The Impact of Using Whatsapp Groups on Students Assignment Quality at The Journalism Study Program - Abdullah Ali; Hanang Septioyudho; Wahyunengsih (CV. Ulil Albab Corp, 2023)
The development of information technology creates very rapid changes in human life. Especially in the field of education, this can be seen from the use of the WhatsApp group application that is used in lectures. Our observations at the Syarif Hidayatullah State Islamic University campus show that all lecturers and students use whatsapp groups in carrying out lectures. The purpose of this study was to determine the effect of Whatsapp Group on the value of the History of Islamic Civilization course for students of the journalism study program for the 2021/2022 academic year. This type of research is included in the type of qualitative research. The research method used is survey and interview. Our survey is to limit the object of our research study. We use this type of interview to describe student satisfaction descriptively with the use of WhatsApp Groups in the History of Islamic Civilization course. In addition, we also ask for permission from Mr. Zakaria to collect data on the value of journalism students for the 2021/2022 academic year. We also questioned the obstacles to using whatsapp groups in the History of Islamic Civilization lecture. Based on the results of our study, we got a positive result. The average value of the History of Islamic Civilization in the journalism study program gets a B and A grade. This value fulfills the credit score for the Islamic History course. However, we found problems in using WhatsApp Groups. In the form of difficulty controlling students in lecture activities, lack of capacity to send video durations on whatsapp., image quality when sent to WhatsApp becomes bad, and fills cellphone memory because of the large amount of material.